2015
DOI: 10.1002/14651858.cd006118.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for psychotic symptoms concomitant with epilepsy

Abstract: Williamson 1986 Williamson PD, Spencer SS. Clinical and EEG features of complex partial seizures of extratemporal origin. Epilepsia 1986;27 Suppl 2:S46-S63. References to other published versions of this review Farooq 2006 Farooq S, Sherin A. Interventions for psychotic symptoms concomitant with epilepsy. Cochrane Database of Systematic Reviews 2006, Issue 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
4
0
3
Order By: Relevance
“…Regarding antipsychotics, the evidence is also scant. A Cochrane Review 51 quotes only a single controlled study investigating olanzapine (10 mg/day) as compared to haloperidol (12 mg/day) in 16 people with epilepsy and psychosis. This was, however, a conference abstract published 15 years ago and the study was never published.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Regarding antipsychotics, the evidence is also scant. A Cochrane Review 51 quotes only a single controlled study investigating olanzapine (10 mg/day) as compared to haloperidol (12 mg/day) in 16 people with epilepsy and psychosis. This was, however, a conference abstract published 15 years ago and the study was never published.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Evidence for the treatment of IIP is limited, as evidenced by a recent Cochrane systematic review [52], which found only one small randomized controlled trial with insufficient power. Expert opinion is that antipsychotics and benzodiazepines are the treatment of choice for brief IIP [2].…”
Section: Pharmacotherapy For Brief and Chronic Interictal Psychosis (Iip)mentioning
confidence: 99%
“…It has been shown that low starting doses and slow titration can be helpful in maximizing the therapeutic potential and reducing the risk of adverse effects. A recently published systematic literature review showed positive results for the use of antidepressants (Maguire et al, 2014) and inconclusive results for the use of antipsychotics (Farooq and Sherin, 2008) in patients with epilepsy. The choice of psychotropic medication in patients with epilepsy requires careful consideration, taking into account the effects of antidepressants and antipsychotics on seizure threshold, as well as their interaction potential with anticonvulsants.…”
Section: Mental Healthmentioning
confidence: 99%